Faktor – Faktor yang Mempengaruhi Loyalitas Pelanggan dan Kepuasan Pelanggan Sebagai Intervening pada Restoran Richeese Factory Kabupaten Tangerang - Berlina Pebrianti; Dihin Septyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In an era of globalization and increasingly competitive business today, business conditions can be said to be highly competitive. Customer satisfaction is a very important factor in fast food restaurants. High customer satisfaction can build a good restaurant reputation thus increasing customer loyalty and can ultimately drive long-term business growth. The research aims to understand the factors that influence customer loyalty and customer satisfaction as intervening on a fast food richeese factory restaurant in Tangerang district with a focus on variables such as quality of service, product quality, physical environment and brand image. This method of research uses a descriptive approach of causality with quantitative methods and applies purposive sampling techniques distributed through a questionnaire to 125 respondents against customers of the Richeese factory district of Tangerang, and has made at least 2 purchases in a month. The results of this research prove that the quality of service, product quality, physical environment, and brand image have a positive and significant influence on customer satisfaction. Furthermore, quality service, quality of product, brand image, and satisfaction of customers have a good and significant effect on customer loyalty. Then on the mediation test, customer satisfaction can mediate the quality of service, product quality, physical environment, and brand image. This research contributes to fast food restaurants to focus more on customer satisfaction and customer loyalty. The research suggested that future researchers conduct a study that covers all outlets, perform a larger data collection of 125 respondents, and use or add promotional and price variables that might influence better results.